The LCOE Evolution and Grid Parity Analysis of Centralized Solar Photovoltaic: A Case Study of Ningxia, China - Mu, Lingling; Gu, Yidan; Guo, Yafeng; Liu, Ping (Frontiers in Energy Research, 2021)
Achieving grid parity in 2021 is the goal of China’s photovoltaic development, which is not only on the user-side but also on the generation side. Relevant studies indicated that distributed PV has realized grid parity basically in China, while centralized PV, which belongs to the generation side, still has some difficulties in achieving grid parity. Therefore, this paper takes Ningxia Province, which is abundant in solar resources, as the research object, and compares LCOE with traditional coal-fired price to analyze the situation of grid parity of Pingluo project. It is found that this project cannot reach the goal. Then, the future evolution of the local LCOE is analyzed, so as to determine the time of grid parity of Ningxia’s centralized PV power stations. In the calculation of LCOE, without and with environmental benefits as well as general and optimistic forecast are combined into four scenarios. The results show that the centralized PV in Ningxia cannot achieve grid parity in 2021 under the four scenarios. But in addition to the scenario that there are no environmental benefits and is generally forecasted will reach grid parity of generation side in 2023, other situations can achieve the goal in 2022. Moreover, the LCOE with environmental benefits and the optimistic forecast is the lowest.